Adaptive-Reuse of Timber Rowhouses in Hua Takhe Waterfront Community, Bangkok through Gentrification Phenomenon - Dhirasedh , Suchacree; Boonprasong, Peeraya (Asian Creative Architecture, Art and Design, 2023)
This research aimed to explore role of gentrification affecting to change in architecture, society, and community lifestyles, through adaptive-reuse of existing timber rowhouses, including analyzing through attitudes of residents and entrepreneurs resulting from gentrification. To discuss on changes of new uses occurring in timber rowhouses, Hua Takhe community, data was collected by fieldwork, interviews, surveys, literature review, and relevant documents. From studying the phenomenon of gentrification, questions arise regarding how this phenomenon and people’s attitudes contribute to use transformation of timber rowhouses in the community. In comparative study on buildings that have been repurposed by entrepreneurs, it was found that the gentrification has led to amendments of physical and architecture in through community’s usage of space. These changes are intended to accommodate the new usage respond to the trend of nostalgia tourism. Consequently, new activities can emerge to the local that traditionally coexist. It was found that changes in architectural characteristics and usage of timber rowhouses are in line with the objectives of usage that respond to the growth of tourism. When analyzing with methods of changing physical characteristics of the building, it was found that entrepreneurs often repair and renovate buildings similar to the original style - facade and structure. With the idea of façade preservation, the overall environment is consistently maintained with the context while uses maybe varies demonstrating coexistence between entrepreneurs and the people in the community. In summary, attitudes of the entrepreneurs are importantly for the development and preservation of the community, both economically and socially. Through gentrification, good knowledge and understanding of the situation can lead to strong community in terms of harmonization between entrepreneurs and local way of living.